Thirty-day rehospitalizations among elderly patients with acute myocardial infarction: Impact of postdischarge ambulatory care. Issue 24 (June 2018) - Zabawa, Claire; Cottenet, Jonathan; Zeller, Marianne; Mercier, Grégoire; Rodwin, Victor G.; Cottin, Yves; Quantin, Catherine
Abstract : Abstract: Rehospitalization after acute myocardial infarction (AMI) is common in elderly patients. It increases morbimortality and health care expenditures. The association between ambulatory care after discharge for AMI and rehospitalization has never been studied in France. We analyzed the impact of ambulatory care on rehospitalization of elderly patients (≥65 years) within 30 days after hospital discharge. We conducted a nationwide population-based study of elderly patients hospitalized with a main diagnosis of AMI in France between 2011 and 2013. We excluded patients hospitalized for AMI in the previous year and those who died during the index hospitalization or within 30 days after discharge. The primary outcome was the first all-cause 30-day rehospitalization in an acute care hospital. Individual and neighborhood-level variables were compared among rehospitalized and nonrehospitalized patients. Determinants of 30-day rehospitalization were identified using logistic regression models. Among the 624 eligible patients, 137 (22.0%) were rehospitalized within 30 days after discharge. In multivariate analyses, chronic kidney failure (odds ratio [OR] 1.88; 95% confidence interval [CI], 1.01–3.53) was an independent predictor of 30-day rehospitalization. We found no association among deprivation and spatial accessibility measures and 30-day rehospitalization. The purchase of lipid-lowering drugs prescription within 7 days after discharge was associated with a reduced risk of 30-day rehospitalization (OR 0.53; 95% CI, 0.36–0.79). This study highlights the role of coordination among hospital and primary care physicians in post-AMI discharge and follow-up among elderly patients. Specifically, targeted interventions to reduce 30-day rehospitalizations should focus on patients with comorbidities and use of prescription drugs after hospital discharge. Abstract : Supplemental Digital Content is available in the text